PI Control Application for Low Speed Stepper Motor in Medical Infusion Pump for Flow Rate Stability - In'am, Muhammad Achsanul; Sutarna, Nana; Hamijaya, Astri Era (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
An infusion pump is an intravenous injection machine for administering high-alert type drugs. Failure to administer this type of drug can result in the patient's death. One of the causes of failure is disturbances in the infusion fluid flow rate, which is influenced by the performance of the stepper motor. This research proposes a PI control design for controlling flow rate stability in infusion pump machines. PI is applied by simulating Simulink using the Ziegler Nicholes type 1 tuning method and creating a 1st-order transfer function using the Cian Cone method. The system is also applied directly to the hardware and tested using standard medical calibration tools. The simulation results show that the PI control can reach the set point and maintain stability with a rise time of 19.49 seconds and a settling time of 32.39 seconds. In actual testing of the infusion pump machine with PI control, the average level of accuracy of the flow rate reached 98%, and the stability reached below 0.3 ml/h. This proves that the infusion pump that has been successfully created can be used to administer high-alert drugs precisely according to the dosage and can be used for a long time with constant delivery quality.